Malha amostral para cafeicultura de precisão - Faria, Rafael de Oliveira (2019)
The area planted with coffee trees in Brazil is not changing in recent years, differently the production that has been expanding. This is linked directly the increased productivity of the areas with investment in new technologies by farmers. Precision agriculture is one of the tools consolidated in annual crops and rise in perennial crops such as coffee. In the last nine years of research, this management has been named precision coffee farming. Superior in georeferenced soil chemical analysis and variable rate fertilizer applications, the productivity map is of great importance for the precision coffee farming cycle. Thus, this work, of sampling and spatial interpolation of soil, plant and productivity attributes, has the prerogative to survey thematic maps of soils and plant, using two points per hectare grid. The rehearsal of soil attribute, leaf and yield maps was done in 54.65 ha crop, during two consecutive harvests, with fertilization at varying rates, according to recommendations based on the soil attribute maps, with accompaniment of the maps. of leaf analysis, seeking to establish correlation between the evaluated parameters and to determine parameters for the management of the coffee crop. It is concluded that the two-point sampling per hectare grid was enough to verify the spatial dependence of soil, leaf and yield attributes, being indicated for application in precision coffee farming.